Analisis Kebutuhan Media Pembelajaran Looseparts dalam Implementasi Meningkatkan Kemampuan Kognitif Anak Usia Dini - Nuza Hery Setyani; Ida Dwijayanti; Sumarno Sumarno (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2023)
Improving cognitive skills in early childhood is an important part of their development. An effective learning environment can be a means to that end. One type of learning media that can be used is loose parts. Looseparts is a term used to describe materials or objects that have certain properties and can be used creatively in children's play and learning. These materials are often available in a variety of sizes, shapes, textures, and flexibility, so that children can manipulate them, combine them, and use their imagination to create a variety of possibilities for play and exploration. Examples of looseparts are rocks, sand, branches, pieces of wood, leaves, paper, shells, rubber bands, rubber rings, ropes, boxes and other everyday objects. The purpose of writing this article is to find out the analysis of the needs of looseparts learning media in the implementation of improving early childhood cognitive skills, the data collection method in this study is by distributing questionnaire sheets, interviews and documentation. When children play with looseparts, they can develop various cognitive aspects such as categorization, problem solving, visualization, abstract thinking, spatial skills, and comprehension. It is important to give children time and space to freely explore the open passages so that they can develop cognitive skills in a natural and interesting way